Eco-friendly synthesis and photodegradation of hierarchical nanostructures of β-FeOOH and α-Fe2O3. Issue 108 (19th October 2015) - Li, Zan; Meng, Guoli; Chen, Rufen; Song, Xiuqin
Abstract : β-FeOOH and α-Fe2 O3 with different morphologies were synthesized via a facile method using urea or saccharide as the organic matrix. Abstract : Hierarchical nanostructures of β-FeOOH and α-Fe2 O3 with different morphologies were successfully synthesized via a facile and green hydrolysis-aging method using urea or saccharide as the organic matrix. Experimental results showed that the well crystallized β-FeOOH and α-Fe2 O3 could be obtained without higher temperature processing. Systematic control of the morphology and microstructure of the products was achieved by regulating the aging time and the concentration of the organic matrix. The amount of saccharide was very important in stabilizing metastable β-FeOOH. The formation mechanism of various morphologies and the cause of β-FeOOH being stabilized were tentatively proposed on the basis of the evolution of the structure and morphology, along with variation of the reaction conditions. Also, degradation efficiencies of the α-Fe2 O3 and β-FeOOH with different morphologies toward methylene blue were preliminarily investigated, revealing that as-obtained α-Fe2 O3 and β-FeOOH possessed promising photodegradation activity and had potential application in wastewater treatment.